2014
DOI: 10.1007/s00464-014-3933-8
|View full text |Cite
|
Sign up to set email alerts
|

Does the cost of robotic cholecystectomy translate to a financial burden?

Abstract: Relative to laparoscopic cholecystectomy, robotic cholecystectomy takes longer and has greater charges. Revenue, EBDIT, and Net Income are similar after either approach; this indicates that costs with either approach are similar. Notably, this is possible because much of hospital-based costs are determined by cost allocation and not cost accounting. Thus, the cost of longer operations and costs inherent to the robotic approach for cholecystectomy do not translate to a perceived financial burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…However, in a study to evaluate and compare cost of care and reimbursement with robotic versus LC, Rosemurgy et al. [11] demonstrated that revenue, earnings before depreciation, interest, and taxes, and net income were similar after either approach, indicating costs with either approach were similar. In another study of cost report and analysis regarding RC, Bedeir et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study to evaluate and compare cost of care and reimbursement with robotic versus LC, Rosemurgy et al. [11] demonstrated that revenue, earnings before depreciation, interest, and taxes, and net income were similar after either approach, indicating costs with either approach were similar. In another study of cost report and analysis regarding RC, Bedeir et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the value proposition is hard to ascertain [11]. Robotic systems/accessory packages tailored to the financial pressures associated with these wellworked out commodity outpatient procedures could be offered making the use of a robotic system more viable from a financial point of view assuming the quality robotquality std issues are favorable [12].…”
Section: Resultsmentioning
confidence: 99%
“…Rosemurgy et al analyzed costs associated with robotic and laparoscopic cholecystectomy at a single institution from the viewpoint of a hospital stakeholder (44). Amortization costs were excluded because purchasing the robot was allocated across the entire surgery department.…”
Section: Rcmentioning
confidence: 99%
“…The top down analysis found a minimum additional cost of $2,600 per procedure (43) while the instrument price examination found equal instrument costs (19). Two studies found no significant difference (19,44) or minor savings of $391 dollars (45).…”
Section: Analysis Of Rcmentioning
confidence: 99%